Perbandingan Pendidikan Islam Perspektif Mahmud Yunus dan Muhammad ‘Athiyah Al-Abrasyi - Juwariyah, Juwariyah; Juwariyah (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
The aim of the study on the thought of Mahmud Yunus and Muhammad Atiyah al-Abrasyi about the definition and components of Islamic Education is meant to know in detail and to identify their ideas about the definition and scope of Islamic education. Given that education is an activity that is required to be able to keep up with the time from the various changes and to be able to answer the challenges of the times in the future, so that the definition and education components should always be reviewed to keep up with the demands of time. Therefore, this research is expected to give a significant contribution to the effort in promoting Islamic education, especially in Indonesia and generally in the Islamic world.